Tobacco Smoke Exposure as Risk Factor in Early Neonatal Death in Mataram, Nusa Tenggara Barat (NTB) - Musrifa; Luh Putu Lila Wulandari; Dewa Nyoman Wirawan (Universitas Udayana, 2014)
Objective: To investigate tobacco smoke exposure as risk factor of early neonatal death in Mataram, NTB. Method: The study design was case control with a total sample of 87 consisting of 29 cases and 58 controls (1:2). Dependent variable was early neonatal death, independent variable was tobacco smoke exposure. Frequency of antenatal visit, family income, delivery complications, anemia and low birth weight were confounding variables. Data were collected through interview and registered cohort data from nine health centres during the period of 1 January-31 December 2013. Data were analyzed by using bivariate and multivariate (logistic regression) to calculate crude OR and adjusted OR. Result: Results of bivariate analysis indicated that tobacco smoke exposure during pregnancy, extent of exposure ≥3 cigarettes/days during pregnancy, and amount of exposure ≥6 cigarettes/days last 24 hours were 2.75 (95%CI: 0.72-10.50); 2.34 (95%CI: 0.77-7.08); and 2.18 (95%CI: 0.65-7.29) respectively, increasing neonatal death but was not statistically significant. Multivariate analysis indicated that tobacco smoke exposure during pregnancy was 1.32 (95%CI: 0.03-69.90). OR of other variables: low birth weight, family income under IDR 1,100,000,- and delivery complications were 204.39 (95%CI: 20.37-2050.07); 7.86 (95%CI: 1.45-42.83) and 7.55 (95%CI: 1.01-56.38) respectively. Conclusion: Tobacco smoke exposure was not statistically significant risk factor, specifically the smoking habits of the husband. Study discovered that low birth weight, family income under IDR 1,100,000,- and delivery complication during birth were statistically significant factors. Further study is needed to confirm these findings.